Rabbit model of intervertebral disc degeneration by external compression device characterized by X-ray, MRI, histology, and cell viability (Medical Journal of Indonesia, 2006)
Appropriate experimental animal models, which mimic the degenerative process occurring in human intervertebral disc (IVD) breakdown and can be used for new treatment studies such as tissue engineering or disc distraction are lacking. We studied the external compression device that used by Kroeber et al to create intervertebral disc degeneration in rabbit model characterized by X-ray, MRI, Histology, and Cell Viability. Ten NZW rabbit were randomly assigned to one of five groups. Intervertebral disc VL4-L5 are compressed using an external loading device, 1.9 MPa. First group rabbit are loaded for 14 days, second loaded for 28 days, thirth group are loaded for 14 days, and unloaded for 14 days, fourth group loaded for 28 days and unloaded for 28 days. The fifth group, rabbits underwent a sham operation. Additional, rabbits were used as sample for cell viability study. In disc height : sample in group one have biggest decreasing of disc height, that is 23.9 unit. In MRI assessment, the worst grade is grade 3. In histological score, the worst group is group three (58.69), and the best is group 4 (45.69). Group one have the largest dead cell, that are 403.5, and the smallest is group four (124.75). Trypan blue staining showed that group four have better viable cell (91.1) compare than group three (86.4). The study conclude disc degeneration can be created by external axial loading for 14 days in rabbit intervertebral disc. Duration of 28 days unloading gave better result for cells to recover. (Med J Indones 2006; 15:199-207)Â Keywords: Rabbit model âintervertebral disc degeneration- external compression device-X-ray, MRI, Histology, and Cell viabilty